Based on C-CHEWS study on the application value of comprehensive perioperative nursing based on scoring in critically ill children with pediatric cardiovascular surgery - Li, Feifei; Mao, Aifang; Niu, Xiaomei; Zhou, Qingqing (Frontiers in Pediatrics, 2025)
ObjectiveTo assess the association of comprehensive perioperative nursing, including early identification based on the Children's Cardiovascular Early Warning Scale (C-CHEWS score), with outcomes in critically ill children undergoing pediatric cardiovascular surgery in an observational setting.MethodsThis study analyzed data from 120 children with congenital heart disease admitted to the Department of Pediatric Cardiovascular Surgery between March 2020 and March 2022. Patients were categorized based on the type of nursing care received: routine care or nursing care incorporating C-CHEWS scoring. The length of hospital stay, pediatric intensive care unit (ICU) monitoring time, disease control status (death, deterioration, and stability), quality of life, incidence of adverse events, and family members’ satisfaction were recorded and analyzed.ResultsThe observed ICU monitoring time and hospitalization duration were significantly shorter in the comprehensive care group (P < 0.05). Disease control rates were higher in the comprehensive care group (76.67%) compared to the routine care group (30.0%) (P < 0.05). Quality of life scores at discharge were improved in the comprehensive care group (P < 0.05). The incidence of adverse events was lower in the comprehensive care group (10.00%) compared to the routine care group (46.67%) (P < 0.05). Family satisfaction with nursing care was higher in the comprehensive care group (96.67%) compared to the routine care group (70.0%) (P < 0.05).ConclusionThe comprehensive perioperative nursing approach, which included the C-CHEWS score, was associated with earlier identification of clinical deterioration, reduced adverse events, and improved family satisfaction in critically ill children undergoing pediatric cardiovascular surgery. These findings support the potential for broader adoption of this nursing model in clinical practice.